2005
DOI: 10.1677/joe.1.06093
|View full text |Cite
|
Sign up to set email alerts
|

The cellular repressor of E1A-stimulated genes mediates glucocorticoid-induced loss of the type-2 IGF receptor in ileal epithelial cells

Abstract: Glucocorticoids induce hypertrophy of the neonatal ileal mucosa but the molecular mechanisms behind this growth induction remain poorly understood. Ileal epithelial cells (IECs) are dependent upon IGF-II for proliferation both in vivo and in culture. The type-2 IGF receptor (IGFR-2) is a lysosomal transport protein that attenuates IGF-IIdriven growth and is highly abundant in the ileum. The cellular repressor of E1A-stimulated genes (CREG) is a secreted phosphoglycoprotein that affects cell fate via ligand bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
2
6
2
Order By: Relevance
“…Recently, CREG1 has also been found to reside in lysosomes where it is processed by cathepsin‐mediated cleavage in fibroblasts . Additionally, it has been colocalized with its putative receptor IGF2R on the plasma membrane in epithelial cells and smooth muscle . In the present study, CREG1 was observed mainly at cell‐cell junctions and an intracellular vesicular compartment in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, CREG1 has also been found to reside in lysosomes where it is processed by cathepsin‐mediated cleavage in fibroblasts . Additionally, it has been colocalized with its putative receptor IGF2R on the plasma membrane in epithelial cells and smooth muscle . In the present study, CREG1 was observed mainly at cell‐cell junctions and an intracellular vesicular compartment in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, after silencing the expression of CREG, other proliferation-related factors kept the cells growing and reproducing, but at a relatively lower rate of proliferation. Our data may conflict with some previous studies that claimed that higher expression of CREG leads to cellular growth suppression in many types of cells [14][15][16][17]. This may be true in some kinds of cells or in some animal models, but it was ascertained that in human GC cells, CREG contributes partly to the overgrown character of cancer cells.…”
Section: Discussioncontrasting
confidence: 99%
“…We speculate that, by virtue of multivalent M6P clusters exposed on opposite sides of the dimer, CREG could induce dimerization of M6P͞IGF2R and thus promote uptake of the receptor from the cell surface. Recent studies have suggested that CREG may regulate M6P͞IGF2R levels in ileal epithelial cells (32). How the internalization of the CREG-M6P͞ IGF2R complex affects cell growth remains unclear.…”
Section: Structural Implications For Interaction With the M6p͞igf2 Rementioning
confidence: 99%